The epigenetic imprinting defect of patients with Beckwith—Wiedemann syndrome born after assisted reproductive technology is not restricted to the 11p15 region. Issue 12 (6th July 2006) - Rossignol, S; Steunou, V; Chalas, C; Kerjean, A; Rigolet, M; Viegas-Pequignot, E; Jouannet, P; Le Bouc, Y; Gicquel, C
Abstract : Background: Genomic imprinting refers to an epigenetic marking resulting in monoallelic gene expression and has a critical role in fetal development. Various imprinting diseases have recently been reported in humans and animals born after the use of assisted reproductive technology (ART). All the epimutations implicated involve a loss of methylation of the maternal allele (demethylation of KvDMR1/ KCNQ1OT1 in Beckwith–Wiedemann syndrome (BWS), demethylation of SNRPN in Angelman syndrome and demethylation of DMR2/ IGF2R in large offspring syndrome), suggesting that ART impairs the acquisition or maintenance of methylation marks on maternal imprinted genes. However, it is unknown whether this epigenetic imprinting error is random or restricted to a specific imprinted domain. Aim: To analyse the methylation status of various imprinted genes ( IGF2R gene at 6q26, PEG1/MEST at 7q32, KCNQ1OT1 and H19 at 11p15.5, and SNRPN at 15q11–13) in 40 patients with BWS showing a loss of methylation at KCNQ1OT1 (11 patients with BWS born after the use of ART and 29 patients with BWS conceived naturally). Results: 3 of the 11 (27%) patients conceived using ART and 7 of the 29 (24%) patients conceived normally displayed an abnormal methylation at a locus other than KCNQ1OT1 . Conclusions: Some patients with BWS show abnormal methylation at loci other than the 11p15 region, and the involvement of other loci is not restricted to patients with BWS born after ART was used. Moreover, the mosaic distribution of epimutations suggests that imprinting is lost after fertilisation owing to a failure to maintain methylation marks during pre-implantation development.